On-line preconcentration of perfluorooctanoic acid and perfluorooctanesulfonic acid by nonaqueous capillary electrophoresis - Knob, Radim; Maier, Vítězslav; Petr, Jan; Ranc, Václav; Sevčík, Juraj (Electrophoresis, 2012)
Separation of major environmental pollutants as perfluorooctanoic acid (PFOA) and perfluorooctanesulfonic acid (PFOS) by capillary electrophoresis is reported for the first time. It is not possible to resolve the solutes in an aqueous media. However, the use of methanol and acetonitrile as the background electrolyte (BGE) solvents allowed their rapid separation in an uncoated capillary. A major effort was put into BGE optimization in respect to both separation efficiency and detection for further on-line preconcentration. 5 mmol.L⁻¹ naphthalene-1-sulfonic acid and 10 mmol.L⁻¹ triethylamine dissolved in ACN/MeOH (50:50 v/v) provided best separation and detection conditions. Next, the large-volume sample stacking and the field-amplified sample injection were applied and compared. Large-volume sample stacking improved limits of detection (LODs) with regard to the standard injection by 69 times for PFOA and 143 times for PFOS with LODs of 280 and 230 nmol.L⁻¹, respectively. Field-amplified sample injection improved LODs 624 times for PFOAand 806 times for PFOS with LODs 31 and 40 nmol.L⁻¹, respectively. Both preconcentration methods showed repeatabilities of migration times less than 1.2% RSD intraday and 6.6% RSD interday. The method was applied on PFOA and PFOS analysis in a sample of river water treated with solid-phase extraction, which further improved LOD toward 5.6 × 10⁻¹⁰ mol.L⁻¹ for PFOS and 6.4 × 10⁻¹⁰ mol.L⁻¹ for PFOA and allows the method to be used for river water contamination screening or decomposition studies.
Keywords: methanol; Solid Phase Extraction; acetonitrily; Electrophoresis, Capillary; chemické látky znečišťující vodu; elektroforéza kapilární; Water Pollutants, Chemical; Solvents; kapryláty; Methanol; Rivers; rozpouštědla; Fluorocarbons; limita detekce; Acetonitriles; řeky; Alkanesulfonic Acids; Caprylates; extrakce na pevné fázi; kyseliny alkansulfonové; Limit of Detection; fluorokarbony